Macromol. Rapid Commun. 20/2018. Issue 20 (18th October 2018) - Chen, Bo Zhi; Ashfaq, Mohammad; Zhu, Dan Dan; Zhang, Xiao Peng; Guo, Xin Dong
Abstract : Inside Front Cover : In article number1800075, Xin Dong Guo and co‐workers design a novel microneedle patch in which the drug‐loaded microneedles are mounted on the corresponding solid microneedle array. These microneedles are fabricated into a "BUCT 60" pattern to celebrate the 60 th anniversary of Beijing University of Chemical Technology.